Psychosocial burden and strains of pedagogues: using the Job Demands-Resources theory to predict burnout, job satisfaction, general state of health, and life satisfaction - Drüge, Marie; Schladitz, Sandra; Wirtz, Markus Antonius; Schleider, Karin (International journal of environmental research and public health, 2021)
The current study examines the Job Demands-Resources theory among pedagogical professionals. A total of 466 pedagogues (n = 227 teachers; n = 239 social workers) completed the Copenhagen Psychosocial Questionnaire online. After testing the questionnaire structure using confirmatory factor analysis, a JD-R-based prediction model to predict effects of strains on the outcome constructs of burnout, job satisfaction, general state of health, and life satisfaction was estimated. The results confirm the questionnaire structure (RMSEA= 0.038; CFI = 0.94) as well as the fit of the prediction model (RMSEA = 0.039; CFI = 0.93). The outcome constructs could be predicted by emotional demands, work-privacy conflict, role conflicts, influence at work, scope for decision making, and opportunities for development (0.41 ≤ R² ≤ 0.57). Especially for life satisfaction, a moderator analysis proved the differences between teachers and social workers in the structure of the prediction model. For teachers, quantitative demands and work-privacy conflict are predictive, and for social workers, role conflicts and burnout are predictive. The study offers starting points for job-related measures of prevention and intervention.